THE IMPACT OF ALFIBER MSMES (PINEAPPLE LEAF FIBER WASTE PROCESSORS) ON VILLAGERS IN CIKADU VILLAGE FROM THE PERSPECTIVE OF ECONOMICS, SUSTAINABILITY AND ISLAMIC VALUES - Bismantara Bismantara; Devira Felisya Purnama (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2025)
MSMEs have an important role in driving economic growth, improving community welfare, and maintaining environmental sustainability. This study aims to analyze the impact of Alfiber MSMEs, a pineapple leaf fiber waste processing business in Cikadu Village, on the local economy, environmental sustainability, and the application of Islamic values. This research uses quantitative methods with data collected through questionnaires distributed to 50 respondents in Cikadu Village. The results showed that Alfiber MSMEs had a significant impact on increasing community income and creating jobs, especially for housewives. In addition, Alfiber MSMEs also contribute to the reduction of agricultural waste through environmentally friendly processing. From the perspective of Islamic values, Alfiber MSMEs run their businesses in accordance with the principles of social justice and environmental responsibility. Overall, Alfiber MSMEs show great potential in encouraging economic and social sustainability in Cikadu Village, while maintaining harmony with the environment and Islamic values.